Implementation of the Economic Order Quantity Method in a Web Based Spare Part Inventory Information System - Alvin Handoko; Muhammad Farman Andrijasa; Subhan Hartanto (Sean Institute, 2026)
Jaya Muncul Spare Parts Store still uses a manual recording system which often causes errors in stock management and delays in ordering. This study aims to design and build a web based inventory information system using the Economic Order Quantity (EOQ) method to assist in decision making for ordering spare parts. The system was developed with the Laravel framework and MySQL database using an Agile approach that allows an iterative development process. Blackbox testing results show that all functions run well, while the User Acceptance Test (UAT) obtained an average score of 89.97% in the “very good” category. The implementation of the EOQ method is proven to help make purchasing decisions, reducing the risk of stockouts and overstock. Integration of the Reorder Point (ROP) feature as a minimum notification, Safety Stock, and prediction of prices, demand, and stock of goods with Simple Moving Average (SMA). This system is considered effective as a tool to determine the number of purchases of goods at Toko Sparepart Jaya Muncul.